Feasibility and psychometric quality of smartphone administered cognitive ecological momentary assessments in women with metastatic breast cancer - Ashley M Henneghan; Emily W Paolillo; Kathleen M Van Dyk; Oscar Y Franco-Rocha; Soyeong Bang; Rebecca Tasker; Tara Kaufmann; Darren Haywood; Nicolas H Hart; Raeanne C Moore (Digital Health)
Objective Metastatic breast cancer (MBC) is associated with burdensome side effects, including cognitive changes that require ongoing monitoring. Cognitive ecological momentary assessments (EMAs) allow for assessment of individual cognitive functioning in natural environments and can be administered via smartphones. Accordingly, we sought to establish the feasibility, reliability, and validity of a commercially available cognitive EMA platform. Methods Using a prospective design, clinical cognitive and psychosocial assessments (cognitive batteries; patient reported outcomes) were collected at baseline, followed by a 28-day daily EMA protocol that included self-ratings for symptoms and mobile cognitive tests (memory, executive functioning, working memory, processing speed). Satisfaction and feedback questions were included in follow-up data collection. Feasibility data were analyzed using mixed descriptive methods. Test-retest reliability was examined using intraclass correlation coefficients (ICCs) for each EMA, and Pearson's correlation were used to evaluate convergent validity between cognitive EMAs and baseline clinical cognitive and psychosocial variables. Results Fifty-one women with MBC ( n  = 51) completed this EMA study. High satisfaction (median 90%), low burden (median 19%), high adherence rates (mean 94%), and 100% retention rate were observed. ICCs for cognitive tests of working memory, executive function, and processing speed were robust (>0.90) and ICC for memory tests acceptable (>0.66). Other correlational findings indicated strong convergent validity for all cognitive and psychosocial EMAs. Conclusion Cognitive EMA monitoring for 28 days is feasible and acceptable in women with MBC, with specific cognitive EMAs (mobile cognitive tests; cognitive function self-ratings) demonstrating strong reliability and validity.